Ideological Battles Ahead of The First General Election in South Sulawesi - Amri, Khaerul; Daeng Makkelo, Ilham; Amir, Amrullah (Riviera Publishing, 2023)
This study focuses on the ideological struggle in the 1955 elections in South Sulawesi. The practice of democracy made SARA the main menu of its implementation. Collected in electoral district twelve, South Sulawesi was in a tense political situation—the relaxation of the rules for organizing elections added to the dark traces of organizing this democratic party. The historical method is used in this research, which formulates research problems from a historical perspective. The procedures include searching and collecting sources (heuristics), source criticism (selection of materials), interpretation and comparison, and presenting or writing history (historiography). The results of this study show that the Masyumi party benefited from the pre-election situation in South Sulawesi. First, political campaigns were organized under the guidance of religion. Second, several Regional Heads affiliated with the Masyumi Party and election organizers facilitated Masyumi's interests toward the peak of power. Third, the interpretation of government regulations and circulars gave birth to the struggle strategy of the Star Moon banner. Fourth, Muhammadiyah's bipolar role in the Election Winning Action Committee.